Ortografska adaptacija modela šest europskih jezika u hrvatskome - Menac, Antica (Array, 2000)
The authors present the orthographic adaptation of models from six European donor languages (French, German, English, Russian, Italian and Hungarian) in Croatian as the recipient language. The analysis is based on the theory of languages in contact by Rudolf Filipović. The orthographic form of the replica is formed on the basis of a)pronunciation of the model, b)spelling of the model, c) combination of pronunciation and spelling, d)the influence of an intermediary language.